Wear-resistant and acid-and-alkali-resistant composite polishing pad and preparation method thereof

CN119238361BActive Publication Date: 2026-10-30SHANXI RES INST OF SYNTHETIC MATERIALS IND TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411551607.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2026-10-30
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

为了完全满足这四大要求,抛光垫也发展成为包括聚氨酯抛光垫、无纺布抛光垫、绒毛结构复合型抛光垫综合品类,而绒毛结构复合性抛光垫的研究和开发是最具有挑战性的,国内对于这类抛光垫,目前只能开发出中低端产品,对于需要耐强酸强碱强氧化的抛光垫,暂时国内未有成功案例

Benefits of technology

[0024]第一,提高了材料的耐酸性能和耐磨性:本发明采用的聚酯多元醇和聚合物多元醇(POP),和多异氰酸酯(包括二异氰酸酯)进行同步预聚的方式(一步法)制备,采用此方法得到了一种新型聚氨酯共聚体,同时通过低分子量多元醇的加入调节聚氨酯树脂的粘度。POP的加入一方面可以提升产品的强度,提高耐磨性,另一方面,局部改善聚酯多元醇不耐水解的弊端,从结构上提升抛光材料的强度和耐酸碱性能,进而提升产品的耐磨性。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a wear-resistant and acid-and-alkali-resistant composite polishing pad and a preparation method thereof. Polyester polyol, polymer polyol, low-molecular polyol, polyisocyanate, non-woven fabric or mesh cloth, organic solvent, defoaming agent, filler, pigment, non-ionic surfactant, fast penetrating agent and expandable microencapsulated plastic are used as main raw materials to carry out a polymerization reaction on polyester polyol, polymer polyol, low-molecular polyol and polyisocyanate, and after polyurethane resin is formed, a solution is prepared by using the organic solvent, and the internal additive is added. Then, a layer of polyurethane glue solution is formed on the surface of the non-woven fabric by using a scraping coating or complete immersion process, and the mixed solution of DMF and water is used for solidification, and then water washing and drying are continuously completed. The organic solvent in the polyurethane resin solution is replaced by water, the load bearing property of the product is improved, and the product has the common advantages of closed pores and open pores. The application has the advantages of stable and controllable production process, long service life of the product and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of functional polymer materials technology, specifically relating to a wear-resistant and acid- and alkali-resistant composite polishing pad and its preparation method, which is mainly used for fine polishing of components such as silicon carbide substrates, sapphire substrates, ceramic substrates, and semiconductor thin films. Background Technology

[0002] With the rapid development of the semiconductor industry, products are demanding increasingly higher chip density and precision. This necessitates substrates with higher precision, superior surface flatness, and extremely low friction coefficients. Surface polishing technology is a key process for solving semiconductor wafer surface quality issues. The surface polishing process requires materials such as polishing pads, polishing slurries, and dressers, with polishing pads being the most technically challenging and complex to control. Their main functions in the polishing process include: ① effectively and evenly delivering the polishing slurry to different areas of the polishing pad; ② smoothly removing reactants and debris after polishing, achieving a removal effect; ③ maintaining a thin film of polishing slurry on the surface of the polishing pad to ensure sufficient chemical reaction; and ④ maintaining a stable polishing process and preventing surface deformation to obtain a better wafer surface morphology. To fully meet these four requirements, polishing pads have evolved into a comprehensive category including polyurethane polishing pads, non-woven polishing pads, and pile-structure composite polishing pads. The research and development of pile-structure composite polishing pads is the most challenging. Currently, China can only develop low- to mid-range products for this type of polishing pad. There are currently no successful cases in China for polishing pads that require resistance to strong acids, strong alkalis, and strong oxidation. Summary of the Invention

[0003] The purpose of this invention is to address the lack of high-precision, high-wear-resistant, and strong acid and alkali-resistant polishing pads in China, and to propose a wear-resistant and acid and alkali-resistant composite polishing pad and its preparation method. This invention can solve the problems of polishing pads and manufacturing processes in this area. By innovating in raw material formulation and molding process, it improves the overall performance of the product and achieves high-quality polishing for components with high requirements.

[0004] The technical solution of the present invention is: a wear-resistant and acid-alkali resistant composite polishing pad, the composition and content of which by mass parts are: 20-30 parts of polyurethane resin, 70-80 parts of organic solvent, 1-3 parts of nonionic surfactant, 0.5-3 parts of fast penetrant, 1-2 parts of silicone oil defoamer, 5-8 parts of filler, 3-7 parts of expandable plastic microspheres, and appropriate amount of pigment.

[0005] The polyurethane resin is prepared from the following raw materials in the indicated mass ratios: 100 parts polyester polyol, 31-49 parts polymer polyol, 5.6-10.9 parts low molecular weight polyol, and 43.3-55.5 parts polyisocyanate.

[0006] The method for preparing the polyurethane resin is as follows:

[0007] 100 parts by weight of the above-mentioned polyester polyol and 31-49 parts by weight of the polymer polyol were slowly added to a three-necked flask containing DMF at a temperature of 40-45°C. After stirring evenly, 43.3-55.5 parts by weight of the above-mentioned polyisocyanate were added to the three-necked flask. The temperature was raised to 70°C and reacted for 40-60 minutes. The temperature was then raised to 80°C and reacted for two hours to obtain a prepolymer with an NCO content in the range of 3%-5%. Then, 5.6-10.9 parts by weight of the aforementioned low molecular weight polyol were added to adjust the backbone and hard segment content of the polyurethane resin molecular chain so that the final polyurethane resin had an -NCO:-OH ratio between 1:1 and 1.05:1. The reaction temperature during the entire prepolymerization process did not exceed 80°C. After the reaction was completed, the resin was degassed for half an hour and then protected with nitrogen gas to obtain the polyurethane resin for later use.

[0008] Furthermore, the polyester polyol is an aromatic polyester polyol or an aliphatic polyester polyol, with a relative molecular weight between 1000 and 2000 g / mol, an acid value of less than 0.5 mg KOH / g, and a moisture content of less than 0.05%.

[0009] Furthermore, the aliphatic polyester polyol is polybutylene adipate diol 1000.

[0010] Furthermore, the polymer polyols mentioned are POP H45, POP10, and POP13 from Dexin Federal Chemical Industry Co., Ltd.

[0011] Further, the polyisocyanate is one or more of diphenylmethane diisocyanate (MDI), toluene diisocyanate (TDI), hexamethylene diisocyanate (HDI), or diphenylmethane diisocyanate oligomers.

[0012] Furthermore, the expandable plastic microspheres are POLYCHEM 120DU15 or 120DU25 from the American company.

[0013] Furthermore, the organic solvent is selected from N,N-dimethylformamide or methyl ethyl ketone;

[0014] Furthermore, the silicone oil defoamer is selected from polyether siloxanes;

[0015] Furthermore, the nonionic surfactant is selected from fatty alcohol polyoxyethylene ethers or fatty acid polyoxyethylene esters;

[0016] Furthermore, the rapid penetration agent is selected from C90 or OEP-70;

[0017] Furthermore, the filler is one or more of polishing powders such as silica, titanium dioxide, and diamond powder with a particle size ≤1μm, wherein the particle size is preferably between 0.05-0.5μm, and the color can be matched according to market requirements.

[0018] The method for preparing the wear-resistant and acid / alkali-resistant composite polishing pad of the present invention includes the following steps:

[0019] Step (1) Dissolve the prepared polyurethane resin using DMF to prepare a solution with a solid content of 20% to 30%. Then add 1 to 2 parts of silicone oil defoamer, 1 to 3 parts of nonionic surfactant, 0.5 to 3 parts of fast penetrant, appropriate amount of pigment, and 3 to 7 parts of expandable plastic microspheres to the solution. Mix thoroughly and evenly, and control the viscosity at 3000 to 4000 mPa·s. Purge with nitrogen to obtain a polyurethane resin solution for later use.

[0020] Step (2) Prepare a mixture of DMF and water with a DMF concentration of 15% to 20%;

[0021] Step (3) Using the conventional wet production process, a layer of polyurethane resin solution obtained in step (1) is continuously coated on the surface of the nonwoven fabric using a scraping process, and then slowly immersed in the mixture obtained in step (2) at a temperature of 35-40℃. An ultrasonic displacement device is used for displacement, and under the action of silicone oil defoamer, nonionic surfactant and fast penetrant, the DMF in the polyurethane resin solution is replaced by water to form open-cell bubbles.

[0022] After the open-cell foam from step (3) is solidified in step (4), it is washed and ironed again, and finally placed in an oven at a temperature of 135-140℃. The heat causes the expandable plastic microspheres to expand and foam, forming cavities and closed-cell structures inside. After the cavities and closed-cell structures are completely solidified, a wear-resistant and acid-alkali resistant composite polishing pad is obtained.

[0023] The present invention has the following advantages:

[0024] First, it improves the acid resistance and abrasion resistance of the material: This invention uses a one-step method to simultaneously prepolymerize polyester polyols and polymeric polyols (POPs) with polyisocyanates (including diisocyanates). This method yields a novel polyurethane copolymer, and the viscosity of the polyurethane resin is adjusted by adding low molecular weight polyols. The addition of POPs can improve the product's strength and abrasion resistance, and also locally mitigate the drawback of polyester polyols' poor hydrolysis resistance, structurally improving the strength and acid and alkali resistance of the polishing material, thereby enhancing the product's abrasion resistance.

[0025] Secondly, a novel formulation combination and molding structure are provided. Expandable microencapsulated plastic microspheres are added to the polyurethane resin solution formulation, enabling the simultaneous existence of open and closed pores. The open-pore structure is formed by replacing DMF in the polyurethane resin solution with water. The open-pore structure can absorb polishing liquid and polishing residue, reducing surface residue accumulation and preventing quality problems of polishing elements. At the same time, through a drying process, the expandable plastic microspheres form closed pores at high temperature, improving the load-bearing capacity of the material and adjusting the compression ratio of the polishing pad. This allows the polishing element and polishing pad to fit completely, improving polishing efficiency and polishing quality.

[0026] Third, a process method for rapid displacement and formation of microporous structures is provided: using an ultrasonic device to resonate with water, the water is rapidly displaced under the action of silicone oil defoamer, nonionic surfactant and fast penetrant to form a uniformly distributed, finely pored finger-like microporous structure. Detailed Implementation

[0027] Example 1:

[0028] Step 1: Preparation of polyurethane resin: 1000g of polybutylene adipate diol 1000 and 311.1g of polymeric polyol POP H45 were respectively added to a three-necked flask containing DMF. The temperature was 40-45℃, and the temperature was strictly controlled not to exceed 60℃. After stirring evenly, 433g of MDI 100 was slowly added to the three-necked flask. The temperature was raised to 70℃ and reacted for 40-60 minutes. The temperature was then raised to 80℃ and reacted for two hours to obtain a prepolymer with an NCO content of 3%. Then, 500g of the 3% NCO prepolymer was taken out, and 16.1g of 1,4-butanediol was added to adjust the backbone and hard segment content of the polyurethane molecules so that the NCO:-OH ratio of the final polyurethane resin was 1:1. The reaction temperature of the prepolymer did not exceed 80℃ throughout the process. After the reaction was completed, the mixture was degassed for half an hour and then protected with nitrogen gas.

[0029] Step 2: Preparation method of polyurethane resin DMF solution: Take 200g of the prepared polyurethane resin and dissolve it in 800g of DMF. Stir evenly, then add 2% silicone oil defoamer, 1% S80, 0.5% rapid penetrant, 5% 0.08-micron silica and 5% expandable plastic microspheres in sequence to prepare a polyurethane resin solution with a solid content of 20%. The viscosity is controlled at about 3000mps.a. After stirring evenly, degas and set aside.

[0030] Step 3: Preparation of Composite Polishing Pad: The pre-treated nonwoven fabric is placed horizontally on a coating machine, and then polyurethane resin solution is coated onto the surface of the nonwoven fabric with a thickness controlled at 1.3 micrometers. Then, it is immersed in a pre-prepared 15% concentration DMF aqueous solution at 35℃ to fully complete the displacement process. The nonwoven fabric is then placed in a water tank for final washing. The concentration of DMF in the washing tank is controlled below 1%. After high-temperature ironing, it is finally placed in an oven at 135℃ for 40 minutes to remove residual water and DMF, and to allow the expandable plastic microspheres to expand and foam, forming closed cavities for support. After baking, it is cut and roughened to form the final composite polishing pad. After testing, the polyurethane layer thickness is 0.3 micrometers, the hardness is 66 Shore A, and the polishing roughness reaches 0.02nm. Under the polishing action of a polishing solution containing potassium permanganate at pH 13 and mechanical polishing, the polishing cycle can reach 122 hours, during which no surface delamination or debris shedding occurs.

[0031] Example 2:

[0032] Step 1: Preparation of polyurethane resin: 1000g of polybutylene adipate diol 1000 and 311.1g of polymeric polyol POP H45 were respectively added to a three-necked flask containing DMF. The temperature was 40-45℃, and the temperature was strictly controlled not to exceed 60℃. After stirring evenly, 433g of MDI 100 was slowly added to the three-necked flask. The temperature was raised to 70℃ and reacted for 40-60 minutes. The temperature was then raised to 80℃ and reacted for two hours to obtain a prepolymer with an NCO content of 3%. Then, 500g of the 3% NCO prepolymer was taken out, and 16.1g of 1,4-butanediol was added to adjust the backbone and hard segment content of the polyurethane molecules so that the NCO:-OH ratio of the final polyurethane resin was 1:1. The reaction temperature of the prepolymer did not exceed 80℃ throughout the process. After the reaction was completed, the mixture was degassed for half an hour and then protected with nitrogen gas.

[0033] Step 2: Preparation method of polyurethane resin DMF solution: Take 200g of the prepared polyurethane resin and dissolve it in 466.6g of DMF. Stir evenly, then add 1% silicone oil defoamer, 3% S80, 1.5% rapid penetrant, 5% 0.08-micron silica and 7% expandable plastic microspheres in sequence to prepare a polyurethane resin solution with a solid content of 30%. The viscosity is controlled at about 3300 mps.a. After stirring evenly, degas and set aside.

[0034] Step 3: Preparation of Composite Polishing Pad: The pre-treated nonwoven fabric is placed horizontally on a coating machine, and then polyurethane resin solution is coated onto the surface of the nonwoven fabric with a thickness controlled at 1.3 micrometers. Then, it is immersed in a pre-prepared 15% concentration DMF aqueous solution at 40℃ to fully complete the displacement process. The nonwoven fabric is then placed in a water tank for final washing. The concentration of DMF in the washing tank is controlled below 1%. After high-temperature ironing, it is placed in an oven at 135℃ for 40 minutes to remove residual water and DMF, and to allow the expandable plastic microspheres to expand and foam, forming closed cavities for support. After baking, it is cut and roughened to form the final composite polishing pad. After testing, the polyurethane layer thickness is 0.5 micrometers, the hardness is 68 Shore A, and the polishing roughness reaches 0.02nm. Under the polishing action of a polishing solution containing potassium permanganate at pH 13 and mechanical polishing, the polishing cycle can reach 125 hours, during which no surface delamination or debris shedding occurs.

[0035] Example 3:

[0036] Step 1: Preparation of polyurethane resin: 1000g of polybutylene adipate diol 1000 and 311.1g of polymeric polyol POP H45 were respectively added to a three-necked flask containing DMF. The temperature was 40-45℃, and the temperature was strictly controlled not to exceed 60℃. After stirring evenly, 555g of MDI 100 was slowly added to the three-necked flask. The temperature was raised to 70℃ and reacted for 40-60 minutes. The temperature was then raised to 80℃ and reacted for two hours to obtain a prepolymer with an NCO content of 5%. Then, 500g of the 5% NCO prepolymer was taken out and 26.8g of 1,4-butanediol was added to adjust the backbone and hard segment content of the polyurethane molecules so that the NCO:-OH ratio of the final polyurethane resin was 1:1. The reaction temperature of the prepolymer did not exceed 80℃ throughout the process. After the reaction was completed, the mixture was degassed for half an hour and then protected with nitrogen gas.

[0037] Step 2: Preparation method of polyurethane resin DMF solution: Take 200g of the prepared polyurethane resin and dissolve it in 466.6g of DMF. Stir evenly, then add 1.5% silicone oil defoamer, 2% S80, 2.5% rapid penetrant, 5% 0.08-micron silica and 7% expandable plastic microspheres in sequence to prepare a polyurethane resin solution with a solid content of 30%. The viscosity is controlled at about 3500 mps.a. After stirring evenly, degas and set aside.

[0038] Step 3: Preparation of Composite Polishing Pad: The pre-treated nonwoven fabric is placed horizontally on a coating machine, and then polyurethane resin solution is coated onto the surface of the nonwoven fabric with a thickness controlled at 1.5 micrometers. Then, it is immersed in a pre-prepared 15% concentration DMF aqueous solution at 40℃ to fully complete the displacement process. The nonwoven fabric is then placed in a water tank for final washing. The concentration of DMF in the washing tank is controlled below 1%. After high-temperature ironing, it is placed in an oven at 135℃ for 40 minutes to remove residual water and DMF, and to allow the expandable plastic microspheres to expand and foam, forming closed cavities for support. After baking, it is cut and roughened to form the final composite polishing pad. After testing, the polyurethane layer thickness is 0.6 micrometers, the hardness is 72 Shore A, and the polishing roughness reaches 0.01nm. Under the polishing action of a polishing solution containing potassium permanganate at pH 13 and mechanical polishing, the polishing cycle can reach 132 hours, during which no surface delamination or debris shedding occurs.

[0039] Example 4:

[0040] Step 1: Preparation of polyurethane resin: 1000g of polybutylene adipate diol 1000 and 311.1g of polymeric polyol POP H45 were respectively added to a three-necked flask containing DMF. The temperature was 40-45℃, strictly controlled not to exceed 60℃. After stirring evenly, 555g of MDI 100 was slowly added to the three-necked flask. The temperature was raised to 70℃ and reacted for 40-60 minutes. The temperature was then raised to 80℃ and reacted for two hours to obtain a prepolymer with an NCO content of 5%. Then, 500g of the 5% NCO prepolymer was taken out, and 25.5g of 1,4-butanediol was added to adjust the backbone and hard segment content of the polyurethane molecules so that the NCO:-OH range of the final polyurethane resin was 1.05:1. The reaction temperature of the prepolymer did not exceed 80℃ throughout the process. After the reaction was completed, the mixture was degassed for half an hour and then protected with nitrogen gas.

[0041] Step 2: Preparation method of polyurethane resin DMF solution: Take 200g of the prepared polyurethane resin and dissolve it in 466.6g of DMF. Stir evenly, then add 3.5% silicone oil defoamer, 2% S80, 2% rapid penetrant, 5% 0.08-micron silica and 4% expandable plastic microspheres in sequence to prepare a polyurethane resin solution with a solid content of 30%. The viscosity is controlled at about 4000 mps.a. After stirring evenly, degas and set aside.

[0042] Step 3: Preparation of Composite Polishing Pad: The pre-treated nonwoven fabric is placed horizontally on a coating machine, and then polyurethane resin solution is coated onto the surface of the nonwoven fabric with a thickness controlled at 1.5 micrometers. Then, it is immersed in a pre-prepared 20% concentration DMF aqueous solution at 40℃ to fully complete the displacement process. The nonwoven fabric is then placed in a water tank for final washing. The concentration of DMF in the washing tank is controlled below 1%. After high-temperature ironing, it is placed in an oven at 140℃ for 40 minutes to remove residual water and DMF, and to allow the expandable plastic microspheres to expand and foam, forming closed cavities for support. After baking, it is cut and roughened to form the final composite polishing pad. After testing, the polyurethane layer thickness is 0.5 micrometers, the hardness is 76 Shore A, and the polishing roughness reaches 0.03nm. Under the polishing action of a polishing solution containing potassium permanganate at pH 13 and mechanical polishing, the polishing cycle can reach 128 hours, during which no surface delamination or debris shedding occurs.

Claims

1. A wear-resistant and acid / alkali-resistant composite polishing pad, characterized in that: Its composition and content by mass parts are as follows: 20-30 parts polyurethane resin, 70-80 parts organic solvent, 1-3 parts nonionic surfactant, 0.5-3 parts rapid penetrant, 1-2 parts silicone oil defoamer, 5-8 parts filler, 3-7 parts expandable plastic microspheres, and appropriate amount of pigment. The polyurethane resin is prepared from the following raw materials in the indicated weight ratios: 100 parts polyester polyol, 31-49 parts polymer polyol, 5.6-10.9 parts low molecular weight polyol, and 43.3-55.5 parts polyisocyanate. The method for preparing the polyurethane resin is as follows: 100 parts by weight of the above-mentioned polyester polyol and 31-49 parts by weight of the polymer polyol were slowly added to a three-necked flask containing DMF at a temperature of 40-45°C. After stirring evenly, 43.3-55.5 parts by weight of the above-mentioned polyisocyanate were added to the three-necked flask. The temperature was raised to 70°C and reacted for 40-60 minutes. The temperature was then raised to 80°C and reacted for two hours to obtain a prepolymer with an NCO content in the range of 3%-5%. Then, 5.6-10.9 parts by weight of the aforementioned low molecular weight polyol were added to adjust the backbone and hard segment content of the polyurethane resin molecular chain so that the final polyurethane resin had an -NCO:-OH ratio between 1:1 and 1.05:

1. The reaction temperature during the entire prepolymerization process did not exceed 80°C. After the reaction was completed, the resin was degassed for half an hour and then protected with nitrogen gas to obtain the polyurethane resin for later use. The polyester polyols mentioned are aromatic polyester polyols and aliphatic polyester polyols, with a relative molecular weight between 1000 and 2000 g / mol, an acid value of less than 0.5 mg KOH / g, and a moisture content of less than 0.05%. The polymer polyols mentioned are POP H45, POP10, and POP13 from Dexin Federal Chemical Industry Co., Ltd.

2. The wear-resistant and acid / alkali-resistant composite polishing pad according to claim 1, characterized in that: The aliphatic polyester polyol is polybutylene adipate diol 1000.

3. The wear-resistant and acid / alkali-resistant composite polishing pad according to claim 1, characterized in that: The polyisocyanate is one or more of diphenylmethane diisocyanate (MDI), toluene diisocyanate (TDI), hexamethylene diisocyanate (HDI), or diphenylmethane diisocyanate oligomers.

4. The wear-resistant and acid / alkali-resistant composite polishing pad according to claim 1, characterized in that: The expandable plastic microspheres are POLYCHEM 120DU15 or 120DU25 from the American company.

5. The wear-resistant and acid / alkali-resistant composite polishing pad according to claim 1, characterized in that: The organic solvent is selected from N,N-dimethylformamide or methyl ethyl ketone; The silicone oil defoamer mentioned above is selected from polyether siloxanes; The nonionic surfactant is selected from fatty alcohol polyoxyethylene ethers or fatty acid polyoxyethylene esters; The rapid penetration agent is selected from C90 or OEP-70; The filler is one or more of silicon dioxide, titanium dioxide, and diamond polishing powder with a particle size ≤1μm, and the color can be matched according to market requirements.

6. A method for preparing the wear-resistant and acid-alkali-resistant composite polishing pad according to any one of claims 1 to 5, characterized in that: Includes the following steps: Step (1) Dissolve the prepared polyurethane resin using DMF to prepare a solution with a solid content of 20%~30%. Then add 1~2 parts of silicone oil defoamer, 1~3 parts of nonionic surfactant, 0.5~3 parts of fast penetrant, appropriate amount of pigment, and 3~7 parts of expandable plastic microspheres to the solution. Mix thoroughly and evenly, and control the viscosity at 3000~4000 mpa.s. Purge with nitrogen to obtain a polyurethane resin solution for later use. Step (2) Prepare a mixture of DMF and water with a DMF concentration of 15%~20%; Step (3) Using the conventional wet production process, a layer of polyurethane resin solution obtained in step (1) is continuously coated on the surface of the nonwoven fabric using a scraping process, and then slowly immersed in the mixture obtained in step (2) at a temperature of 35~40℃. An ultrasonic displacement device is used for displacement, and under the action of silicone oil defoamer, nonionic surfactant and fast penetrant, the DMF in the polyurethane resin solution is replaced by water to form open-cell bubbles. After the open-cell foam from step (3) is solidified in step (4), it is washed and ironed again, and finally placed in an oven at a temperature of 135~140℃. The heat causes the expandable plastic microspheres to expand and foam, forming cavities and closed-cell structures inside. After the cavities and closed-cell structures are completely solidified, a wear-resistant and acid-alkali resistant composite polishing pad is obtained.

Citation Information

Patent Citations

  • Polishing pad and method for producing the same

    CN102152232A

  • Grinding pad for chemical mechanical grinding and preparation method thereof

    CN113024768A